PENDAMPINGAN DIGITAL MARKETING TERHADAP UMKM RAJUT DAN ECOPRINT ‘YEERA COLLECTION’ KELURAHAN WONOREJO, KECAMATAN RUNGKUT, KOTA SURABAYA - Imamah, Fauziyah; Taufiq, M.; Setya Wijaya, Riko (INCIDENTAL : Journal Of Community Service and Empowerment, 2023)
MSME is a sector that plays an important role in the development of the Indonesian economy and has high potential to improve economic welfare. In today's modern era, it turns out that there are still many MSMEs that are slow in their development process. Many obstacles are faced by business actors such as lack of capital, lack of knowledge, marketing strategies that can be considered old-fashioned, to the lack of innovations made to keep up with the times. As a solution to these problems, MSME assistance is needed to increase competitiveness. The world of marketing has changed along with the development of information technology. Marketing strategies that used to be conventional are now starting to spread in the digital world. Digital marketing is interactive marketing that makes it easier for producers, distributors and consumers to make transactions. The field of business that is most in demand by people from various circles today is the fashion sector. UMKM Yeera Collection is one of the small businesses in the Wonorejo Subdistrict that has just been developed which produces knitted and ecoprint fashion products, this UMKM needs assistance because of the lack of knowledge about digital marketing. The method used is a qualitative method, where the method is used to explain the mentoring process. The implementation of this activity aims to enable the Yeera Collection UMKM to understand the importance of digital marketing as a marketing strategy. The implementation was carried out in four stages, namely observation by mapping MSMEs, education through outreach, digital marketing assistance with several steps such as logo and packaging assistance, e-catalog assistance, social media assistance, and online financial report assistance, as well as the final evaluation.